Cape York IIIAB iron meteorite: Trace element distribution in mineral and metallic phases - Koeberl,Christian; Weinke,Helmut H.; Kluger,Friedrich; Kiesl,Wolfgang (1986)
P(論文) Several mineral and metallic phases in a sample from the Agpalilik mass of the Cape York iron meteorite shower have been analysed for major and trace elements using electron microprobe analysis, rapid instrumental neutron activation analysis, instrumental neutron activation analysis, radiochemical neutron activation analysis, thermochemical methods, and secondary ion mass spectrometry. The phases investigated in this way included kamacite, plessite, taenite, troilite, chromite, and schreibersite. In addition, a rare nickel-rich phase has been found and is described in detail. The genetic implications of the presence of the nickel-rich phase (which may be termed nickel-rich taenite, but does not seem to be related to tetrataenite) are very important. A compositional gradient in Ni and Cu distribution is present, with the largest values near the troilite boundary and the lowest near the kamacite boundary. The phase occurs exclusively at the troilite/kamacite interface and is often associated with rhabdite. It seems as if this was one of the last precipitates from a very Ni-rich troilite-taenite liquid, after schreibersite crystallization purged the system for several siderophile elements. This is supported by the distribution of trace elements between troilite, kamacite, and schreibersite. A fractional crystallization history for the origin of Cape York, starting with dendrites, seems plausible. departmental bulletin paper